Treatment of Corneal Alkali Burn with Chestnut Honey, Royal Jelly, and Chestnut Honey-Royal Jelly Mixture - Kursat Atalay; Kubra Serefoglu Cabuk; Ahmet Kırgız; Aysel Kara Caglar (Beyoglu Eye Journal, 2019)
INTRODUCTION[|]The alkaline burn of the cornea usually results in a decreased vision with opacification. In this study, we investigated the potential role of endemic chestnut honey (CH) and royal jelly on corneal healing after an alkaline burn.[¤]METHODS[|]We created an alkaline burn on the center of the corneas of four groups of Wistar rats by applying round filter paper soaked with 1 N NaOH for 30 seconds. The animals were treated with RJ, CH, RJ-CH combination and Na-Hyaluronate (Na-HA) eye drops. We performed a serial evaluation with anterior segment photography on the first, 7th, and 14th days of the experiment. Pathologic examination conducted with hematoxylin and eosin stains and immunostaining for SMA and α4β1 integrin. We evaluated the corneal healing process with a scoring system, which was estimating the degree of corneal edema, the size of the corneal ulcer, and limbal hyperemia.[¤]RESULTS[|]There was no statistically significant difference between groups on the first, 7th, and 14th days concerning the healing scores (p=0.88, p=0.06, p=0.80, respectively). However, there were significantly better scores in the repeated measures of CH (p=0.012) and RJ-CH (p=0.00) groups. The RJ group and Na-HA group did not show a significant difference in repeated measures (p=0.19 and p=0.10, respectively). The α4β1 integrin levels on immunostaining showed a significant difference among groups on the 14th day (p=0.002).[¤]DISCUSSION AND CONCLUSION[|]We found better corneal healing after treatment with the RJ-CH containing eye drops concerning corneal healing sore and α4β1 integrin staining.[¤]